Notice of some rudely chipped Implements of Indurated Sandstone from South Africa, presented to the Museum - Laider, Percy W (Proceedings of the Society of Antiquaries of Scotland, 1912)
A brief account of a variety of implements recovered from South Africa includes chisels, hatchets and scrapers.